OUT-OF-COURT MORTGAGE SETTLEMENT PROCEDURE IN THE LIGHT OF EU LAW AND THE LEGISLATION OF THE USA, ENGLAND, GERMANY AND THE CZECH REPUBLIC - Vladimir Crnjanski (Pravo)
The out-of-court settlement procedure for claims in European continental civil law presents a challenging area of study, both from a doctrinal perspective and in terms of its normative foundation. Therefore, its characteristics are analyzed within the context of EU law, with special attention to the legislation of Germany and the Czech Republic, as well as the legal frameworks of the USA and England. However, the primary focus of this paper is on the out-of-court procedure for the settlement of mortgage-secured claims in the Republic of Serbia, which is examined in light of the relevant provisions of Directive 2014/17/EU of the European Parliament and the Council of February 4, 2014, on credit agreements for consumers relating to residential immovable property (Mortgage Credit Directive 2014/17). While the directive contains numerous provisions, this paper will focus only on those aspects of the Mortgage Credit Directive 2014/17 that are significant for improving certain de lege lata legal rules governing the Serbian out-of-court mortgage settlement procedure. The research employs dogmatic legal and comparative legal methods. The main objective of this paper is to evaluate future legal amendments in the context of the corresponding provisions of the Mortgage Credit Directive 2014/17.